PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS V SDN 18 KAMPUNG DURIAN KOTA PADANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the impact of using animated videos on student learning outcomes in Pancasila education subjects in grade V of SDN 18 Kampung Durian. Using quantitative methods and a non-equivalent control group design, learning outcomes were measured through tests. This study showed a significant increase between before and after the intervention. In the pretest, the top score recorded among students was 96, whereas the lowest score was 52 with an average of 81.4. After using animated video media, posttest scores increased with the highest score reaching 100, the lowest was 80 and an average of 91.5. The t-test obtained a significance value of <0.001, which indicates that the use of animated video learning media significantly affects learning outcomes. Animated videos are proven to be an effective, innovative, fun, and relevant learning medium for improving student learning outcomes.